The impact of raising Cattle in The Totonacapan region of Mexico: historical development and approaches for a sustainable cattle ranching - Ortiz Espejel, B.; Jiménez Marce, R. (Pastos, 2014)
The development of animal husbandry in the northern region of the state of Veracruz, known as the Totonacapan, produced major environmental changes. The highlights of this development are the introduction of cattle in the sixteenth century and African grasses in the second half of the nineteenth century. Environmental changes rapidly ensued between the years of 1940 and 1970 when livestock operations were intensified. The analysis of three case studies allowed us to estimate the impact that livestock intensification initiatives had across the state and to identify elements that would allow for a sustainable model of cattle ranching in this region.